2021
DOI: 10.3390/biology10050407
|View full text |Cite
|
Sign up to set email alerts
|

Musashi–1—A Stemness RBP for Cancer Therapy?

Abstract: The RNA–binding protein Musashi–1 (MSI1) promotes stemness during development and cancer. By controlling target mRNA turnover and translation, MSI1 is implicated in the regulation of cancer hallmarks such as cell cycle or Notch signaling. Thereby, the protein enhanced cancer growth and therapy resistance to standard regimes. Due to its specific expression pattern and diverse functions, MSI1 represents an interesting target for cancer therapy in the future. In this review we summarize previous findings on MSI1′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 135 publications
(230 reference statements)
0
11
0
Order By: Relevance
“…MSI1 has been recognized to be a stem cell marker that mediates a balance between cell selfrenewal and differentiation. Simultaneously, it is also involved in tumorigenesis and has been identified to be highly expressed in various tumor types such as gastric cancer, esophageal cancer, cervical cancer, colorectal cancer, and glioblastoma [48][49][50]. Furthermore, it has been reported that MSI1 can be used as a therapeutic target and diagnostic marker for lung cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…MSI1 has been recognized to be a stem cell marker that mediates a balance between cell selfrenewal and differentiation. Simultaneously, it is also involved in tumorigenesis and has been identified to be highly expressed in various tumor types such as gastric cancer, esophageal cancer, cervical cancer, colorectal cancer, and glioblastoma [48][49][50]. Furthermore, it has been reported that MSI1 can be used as a therapeutic target and diagnostic marker for lung cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins, including OCT4, MYC, KLF4, and SOX2 (Yamanaka factors), are universal, considering that they are typical of both cancer and normal stem cells and are considered essential for stem-related phenotypes [ 107 ]. The regulation of other markers, though, for instance, NANOG, BMI-1, SNAIL, ALDHs, LGR5, CXCR4, REX-1, Musashi-1, LETM1, and C-met, is considered to be dependent on both the cancer type and the specific phenotype of the CSCs that we want to analyze (e.g., drug-resistant, tumorigenic, metastatic) [ 35 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Studying the expression of specific genes both at the transcriptional and translation level, as well as the activity and localization of these proteins, is useful in assessing the enrichment of CSC properties [ 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Downstream proteins of Notch interact with a myriad of different factors involved in other pathways to maintain CSCs and progenitors. One of these factors is Musashi-1, an RNA-binding protein known for its role in CSC maintenance [ 59 ]. Elevated levels of Musashi-1 have been observed in eCSCs and inhibition of this protein results in downregulation of Notch-1 signaling which triggers apoptosis in endometrial cancer cells (ECCs) [ 60 ].…”
Section: Pathways Involved In Ecsc Maintenancementioning
confidence: 99%